2017
DOI: 10.1038/s41598-017-14903-x
|View full text |Cite|
|
Sign up to set email alerts
|

The photoelastic coefficient $${P}_{12}$$ of H+ implanted GaAs as a function of defect density

Abstract: The photoelastic phenomenon has been widely investigated as a fundamental elastooptical property of solids. This effect has been applied extensively to study stress distribution in lattice-mismatched semiconductor heterostructures. GaAs based optoelectronic devices (e.g. solar cells, modulators, detectors, and diodes) used in space probes are subject to damage arising from energetic proton (H+) irradiation. For that reason, the effect of proton irradiation on photoelastic coefficients of GaAs is of primary imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…These prospects are not simply technical because the application in TDBS of the polarimetry, for example, provides access to imaging of the material parameters that are not accessible by common TDBS technique, such as optical refractive index measurements for ordinary and extraordinary light waves and determination of the different components of the photoelastic tensor, including those controlling acousto-optic mode-conversion of probe light 126 . By conducting TDBS at several polarizations of the probe light it has already been possible to reveal spatially inhomogeneous optical anisotropy induced by loading of the material in a DAC 47 and to characterize spatial distributions of different photoelastic parameters of GaAs implanted by energetic protons 127 . Significant physical-technical progress also could be expected through 44 the application of shear CAPs for TDBS imaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These prospects are not simply technical because the application in TDBS of the polarimetry, for example, provides access to imaging of the material parameters that are not accessible by common TDBS technique, such as optical refractive index measurements for ordinary and extraordinary light waves and determination of the different components of the photoelastic tensor, including those controlling acousto-optic mode-conversion of probe light 126 . By conducting TDBS at several polarizations of the probe light it has already been possible to reveal spatially inhomogeneous optical anisotropy induced by loading of the material in a DAC 47 and to characterize spatial distributions of different photoelastic parameters of GaAs implanted by energetic protons 127 . Significant physical-technical progress also could be expected through 44 the application of shear CAPs for TDBS imaging.…”
mentioning
confidence: 99%
“…Significant physical-technical progress also could be expected through 44 the application of shear CAPs for TDBS imaging. Although optoacoustic transducers for shear CAPs are more elaborate than those used for compression/dilatation waves 33,[121][122][123][124][125][126][127][128][129][130][131][132][133] and detection of shear CAPs as well 33,122,133 , their application would provide access to imaging of the complex shear rigidity of inhomogeneous media at nanoscale.…”
mentioning
confidence: 99%
“…From this observation, it is possible to study P 12 alone if the crystallite has an orientation where the Δ i terms are very small. A similar experiment has been undertaken to study the evolution of P 12 in proton irradiated GaAs 33 . Here, we define the anisotropy of the photoelastic tensor α r ¼ 2P 44 =ðP 11 À P 12 Þ, in analogy to the Zener ratio for the elastic tensor.…”
Section: Discussionmentioning
confidence: 99%
“…TBDS has proven to be invaluable tool to study different depth dependent properties of materials [2,3] such as elastic and optical inhomogeneities in disordered films [4][5][6], ion implantation induced modification of interfacial bonding [7], sub-µm textures in materials compressed at megabar pressures [8,9], doping profiles [10], depth-dependent stress [11], imaging of grain microstructure [12,13], and determination of laser-induced temperature gradients in liquids [14]. It has been shown that TDBS is sensitive to ion implantation induced damage in gallium arsenide [15][16][17], diamond [18] and silicon carbide [19] at low fluences.…”
Section: Introductionmentioning
confidence: 99%
“…17 (p) cm −3 1.2×10 18 (p) cm −3 5.9×10 17 (n) cm −3 2.0×10 18 (n) cm −3 Derivative of the dielectric function for different doping types and concentrations. The dielectric function was taken from Casey et.…”
mentioning
confidence: 99%